The antecedents and innovation effects of domestic and offshore R&D outsourcing: The contingent impact of cognitive distance and absorptive capacity - Bertrand, Olivier; Mol, Michael J. (Strategic Management Journal, 2013)
This paper analyzes differences in the antecedents and performance consequences of domestic and offshore R&D outsourcing. Offshore outsourcing is characterized by larger cognitive distance. We find that absorptive capacity from internal R&D allows for more offshore outsourcing and that offshore outsourcing leads to more positive innovation outcomes, especially product innovation.